Kinerja Pelayanan Terminal Terpadu Merak - Anton Hefyansyah; L. Denny Siahaan; Sarinah Sihombing (Institut Transportasi dan Logistik Trisakti, 2020)
Upgrading service in terminal by doing performance evaluation services based on terminal minimum service standard is the purpose of this research. The research was conducted in Merak integrated terminal. The research used quantitative descriptive method with 176 people as samples. The data was analysed using Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA). The first result can be concluded that the value of satisfaction of Merak integrated terminal services is 70,98%. The second result can be concluded that the level of suitability of Merak integrated terminal services does not meet the expectation of service users. The third, it can be concluded that the top service priority improvement consists of clean and odorless toilets, internet network facilities, charging battery facilities, disable facilities, parking lots, green open spaces and facilities for nursing mothers and babies.